Plant genes, genomes, and genetics - Grotewold, Erich; Chappell, Joseph; Kellogg, Elizabeth Anne (John Wiley & Sons Inc., 2015)
Plant Genes, Genomes and Genetics provides comprehensive treatment of all aspects of plant gene expression. Unique in explaining the subject from a plant perspective, it highlights the importance of gene expression in how plants interface with the modern world, and notes the many aspects of gene expression that were first discovered in plants. This reference covers topics ranging from plant genome structure and the key control points in how genes are expressed, to the mechanisms by which proteins are generated and how their activities are controlled and altered by posttranslational modificatio.